Efeitos da suplementação com suco de uva tinto sobre o desempenho físico e estresse oxidativo de corredores e a influência de polimorfismos genéticos - Toscano, Lydiane de Lima Tavares (2019)
Recent studies have demonstrated the ergogenic capacity of purple grape juice by improving physical performance and antioxidant activity in recreational athletes. However, responses to supplementation are divergent, as a minority of athletes do not respond to intervention, and responsive individuals have a large variability in the magnitude of responses related to physical performance. One perspective to clarify this variability is the evaluation of genetic polymorphisms. Thus, the present study investigated whether the SOD3 Arg213Gly, PPARα 7G/C and ACTN3 R577X polymorphisms influence the effects of chronic purple grape juice supplementation on physical performance and redox balance in recreational runners. Additionally, investigated the effects of a single dose of juice on physical performance, oxidative stress, inflammation and muscle damage. For the chronic effects and the influence of the polymorphisms, a clinical-controlled trial was conducted with 30 runners (34±1 years; VO2peak: 50.8±1 ml/ kg/ min) supplemented with grape juice (10ml/ kg/ day) and 10 ingested a control drink (35±2 years; VO2peak: 50.0 ± 2.2 ml / kg / min) for 28 days. Blood samples were collected at baseline and 48 hours after the 28th day of supplementation. The parameters evaluated were running time, total antioxidant capacity (TAC), superoxide dismutase (SOD), protein carbonylation and malondialdehyde (MDA), as well as genetic polymorphisms SOD3 Arg213Gli, PPARα 7G / C and ACTN3 R577X. While for the effects of a single dose, a randomized, double-blind, placebo-controlled clinical trial was conducted with 14 recreational male runners (39±9 years; VO2peak = 55.9 ± 6.5 ml.kg.min) randomized to grape juice and placebo drink (10ml/ kg/ day). Blood was collected, before supplementation, two hours after supplementation, and immediately after the exhaustion test. Exhaustion time, TAC, MDA, creatine kinase (CK), lactate dehydrogenase (LDH), alpha-1-acid glycoprotein (A1AGP) and high-sensitivity C-reactive protein (hs-CRP) were evaluated. Additionally, nutritional status, training loads, psychometric behavior, sleep and rest/ recovery were evaluated for both trials. It was observed for multiple doses of juice, regardless of genotyping, improved exhaustion time (9.2 ± 2.6 minutes; p = 0.02). However, athletes with PPARα GG allele had time decreased (-0.3 ± 1.8 minutes), while athletes with C allele increased 8.7 ± 6.0 minutes (p = 0.02), without changes to oxidative stress. The SOD3 gene revealed only a better performance trend for CC allele (p = 0.06), with lower carbonylation for CC and lower MDA for G allele. Single dose of juice increased run time to exhaustion (18.7%; p = 0.008) and increased TAC (43.6%; p = 0.000) post-exercise. MDA, A1GPA, hs-PCR, CK, and LDH did not change. It is concluded that grape juice has ergogenic effects for both multiple and single doses. Additionally, accompanied by acute increased antioxidant protection, while multiple doses showed a consistent tendency for TAC and SOD. Our findings confirm the variability of responses and indicate that athletes with GG genotype did not obtain the ergogenic effects of grape juice in the running test to exhaustion, indicating that nutrigenetics is a variable that deserves to be considered for sports performance.